Spatial variability in picophytoplankton, bacteria and viruses in waters of the Great Australian Bight (southern Australia). (November 2018) - Patten, Nicole L.; van Ruth, Paul D.; Rodriguez, Ana Redondo
Abstract: The Great Australian Bight (GAB) is a region of great economic and ecological importance to southern Australia, supporting fisheries of national and international importance, and large populations of small pelagic fish and iconic apex predators. There is, however, limited information on the plankton forming the base of the food web and their links to higher trophic levels in the GAB. Bacteria [inclusive of Archaea ], picophytoplankton ( Prochlorococcus, Synechococcus and picoeukaryotes) and viruses were investigated in the central through to the eastern GAB for the first time, across five shelf edge to offshore transects in the austral Autumn of 2013. Downwelling conditions were evident over the region prior to and during the study period. Prochlorococcus numerically dominated picophytoplankton, exceeding Synechococcus and picoeukaryotes on average, by 5-fold and 30-fold respectively. Synechococcus and picoeukaryotes showed a clear shelf edge to offshore trend with highest abundances occurring at the shelf edge. Bacterial abundances showed low variation over the region, but with highest percent of high DNA bacteria (%HDNA) occurring at the shelf edge. Viral abundances closely followed bacteria, however individual viral groups were positively correlated with picophytoplankton groups, suggesting all picoplankton groups were subject to viral infection in GAB waters. Highest total picoplankton biomass occurred in surface waters at the shelf edge (26.5 ± 1.49 µg C L −1 ), with picophytoplankton carbon biomass (PB) and bacterial carbon biomass (BB) each accounting for ~50% of the total picoplankton biomass in the upper 60 m of the water column. Total picoplankton biomass was ~2-fold lower offshore waters, with BB comprising the bulk of the biomass (~72%). For the upper 60 m of the water column, picoeukaryotes accounted for ~51% of PB at the shelf edge, compared to ~24% in offshore waters. Based on our estimated C:Chl a ratios, picoeukaryotes accounted for 32.7 ± 3.0% of Chl a at the shelf edge, compared to 9.1 ± 0.6% in offshore waters. Prochlorococcus dominated PB in offshore waters (~67%), accounting for ~28% of Chl a . Multivariate analyses showed that the best predictors of the picoplankton community were a combination of nitrate and salinity (ρ = 0.704), indicating strong environmental forcing of the picophytoplankton community across the GAB. The elevated PB at the shelf edge, due to the dominance of picoeukaryotes, was a regional feature of the central and eastern GAB during the time of this study. We hypothesize that picoeukaryotes play a critical role in supporting higher trophic levels in GAB shelf edge waters. This study highlights the importance of small plankton in food web dynamics in GAB waters.